1994
DOI: 10.1143/jjap.33.5301
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ferroelectric Bi4Ti3O12 Thin Films by Dipping Pyrolysis of Metal Naphthenates and Micropatterns by an Electron Beam

Abstract: Fabrication of ferroelectric Bi4Ti3O12 thin films was carried out by dipping pyrolysis of metal naphthenates. Single-phase Bi4Ti3O12 thin films with c-axis orientation perpendicular to the substrate surface were fabricated on Pt plates. They exhibited good ferroelectric properties: coercive field of 7.7 kV/cm and remanent polarization of 8.2 µ C/cm2. For the films fabricated on Pt/Ti/ SiO2/Si substrates, however, the Bi2Ti2O7 phase mainly grew because of Ti diffusion into the bismuth titanate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…In the last few years electrical transport on DNAbased polymers has been a topic of intensive research. [19] While natural DNA seems to be a poor electrical conductor, as reported by Gomez-Navarro et al [20] and further confirmed by Storm et al [21] (see reviews on this topic [22] Mercaptopurine is a thiopurine derivative whose structure is closely related to that of oxoderivative guanine, since they differ only in that mercaptopurine has a heteroatom at position 6 and no NH 2 group at position 2 (Fig. 1a).…”
Section: Methodsmentioning
confidence: 64%
“…In the last few years electrical transport on DNAbased polymers has been a topic of intensive research. [19] While natural DNA seems to be a poor electrical conductor, as reported by Gomez-Navarro et al [20] and further confirmed by Storm et al [21] (see reviews on this topic [22] Mercaptopurine is a thiopurine derivative whose structure is closely related to that of oxoderivative guanine, since they differ only in that mercaptopurine has a heteroatom at position 6 and no NH 2 group at position 2 (Fig. 1a).…”
Section: Methodsmentioning
confidence: 64%
“…The sensitivity is ∼9 mC cm −2 (at half the normalized thickness, D 0.5 ) and the contrast is γ ≈ 1.4. Infrared absorption studies of naphthenate materials by Kakimi et al suggest that electron beam exposure results in the creation of bridges at the CO and/or (CH 2 ) n  sites, thereby causing crosslinking and the negative tone behavior 21. These properties are suitable for the creation of design patterns, with the nickel naphthenate acting as a negative resist.…”
Section: Resultsmentioning
confidence: 99%
“…This gives rise to negative tone patterning. 10 It is worth noting that there is no lift-off step in our study and consequently problems associated with this step are bypassed; the result of which is less number of processing steps to get highresolution oxide nanolines.…”
Section: Resultsmentioning
confidence: 99%